Credibility of EMS interest rate policies: a Markov regime-switching approach - Philip Arestis; Kostas Mouratidis (Levy Economics Institute of Bard College, 2002)
The primary objective of this paper is to use the Markov regime-switching modeling framework to study the credibility of monetary policy in five member countries of the European Monetary System (EMS) during the period 1979 to 1998. The five countries examined for this purpose are Austria, Belgium, France, Italy, and the Netherlands. The major innovation of this paper is the use of a Markov regime-switching model with time-varying transition probabilities. The output-gap variability and the inflation variability variables are incorporated into the determination of the monetary policy preferences of individual member countries of the EMS. Empirical evidence is provided to show that although all the countries in our sample followed a credible monetary policy regarding price stability, they had different preferences regarding the trade-off between the stabilization of output-gap variability and inflation variability.
Keywords: 330